Hubungan penguasaan hukum kekekalan energi mekanik dengan hasil belajar fisika siswa pada materi momentum di kelas XI SMA Negeri 5 Padangsidimpuan - Rahman, Abdur; Siregar, S.Si., M.Si, Dwi Aninditya (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2024)
This research aims to know whether there is correlation mechanic constant energy law to students’ achievement in momentum of the XI grade students of SMA Negeri 5 Padangsidimpuan. The method of this research is descriptive method by correlational approach to see the description of both variables. Population of this research is all of the XI grade students of SMA Negeri 5 Padangsidimpuan, consist of 3 classes, it is 105 students. Sampling technique was taken by using random sampling, it is 31 students. The instrument of this research is test for both variables, and it is 20 items. Data was analyzed by two steps. They are descriptive and inferential analysis by using r product formula. The mean of mechanic constant energy law is 76.27, it is good category. The mean of the students’ achievement in momentum is 79.53, it is very good category. Based on the calculation , it was got that r count is 0.736, and r table is 0.355 at 95 % significant. It can be seen that r count is greater than r table ( 0.736 > 0.355 ). It means that there is significant correlation mechanic constant energy law to students’ achievement in momentum of the XI grade students of SMA Negeri 5 Padangsidimpuan